Implementation of discovery learning model Cooperative Learning-Based In Increasing Learning Participation - Ai Tin Sumartini (Journal Civics and Social Studies, 2022)
The current learning process needs to develop all the potential of learners both aspects of attitude, knowledge and skills, so that it is expected to be able to participate in facing various demands of the times in community life, nationhood, statehood. In fact, there are still many monotonous learning processes, lack of student learning participation that has implications for the low learning outcomes obtained. This research aims to find out the application of a cooperative-based Discovery Learning Model in increasing learners' learning participation. Discovery Learning is one of the models developed in 21st century learning. Because with a scientific approach learners are trained to observe various stimuli, identify problems, find their own information, process information, prove information through presentation and formulate generalizations or conclusions. This research method uses the Class Action Research method with the Lewin model implemented in two cycles, describing the process of implementing a cooperative discovery learning model in increasing learners' learning participation.The results showed that the cooperative-based Discovery Learning Model can increase learners' learning participation both individually and in groups from cycle I to cycle II. Likewise, the average postest increases from cycle I to cycle II. This has implications for improving learning outcomes.